Pengaruh Asset Growth, Kebijakan Dividen, dan Struktur Modal terhadap Nilai Perusahaan Sektor Teknologi Terdaftar di Bursa Efek Indonesia Tahun 2021-2023 - Putu Doni Sastrawan; Gede Adi Yuniarta (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study is to determine the effect of asset growth, dividend policy, and capital structure on firm value in technology sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. The background of this study is based on the rapid development of the technology industry in Indonesia, which requires companies to manage resources and finances optimally. Factors such as asset growth, dividend distribution policy, and capital structure are believed to play a significant role in determining a company's value in the eyes of investors. In today's competitive business environment, firm value is one of the most crucial indicators for investors and stakeholders. The research data was obtained from the official IDX website, www.idx.co.id, using a purposive sampling technique. From the selection results, 22 technology companies were selected that met the research criteria. The data collection method was carried out by reviewing the annual financial reports of these companies. Data analysis used classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests to ensure the regression model used met the BLUE (Best Linear Unbiased Estimator) requirements. Hypothesis testing was then conducted through multiple linear regression analysis, t-tests, and coefficient of determination using IBM SPSS 25 for Windows. The results showed that asset growth and dividend policy variables had no effect on firm value. Conversely, capital structure was shown to have a positive and significant influence on the value of technology sector companies. This finding highlights the importance of capital structure decisions in enhancing firm value, especially in the technology industry, where innovation and expansion require strong financial strategies. Therefore, this study contributes to financial managers and investors' consideration of capital structure as a strategic factor in increasing firm value.